INCIDENCE, RISK FACTORS AND OUTCOMES OF ACUTE KIDNEY INJURY IN PRETERM NEWBORNS - Naunova Timovska, Silvana; Bojadzieva, Sonja; Sofijanova, Aspazija; Shuperliska, Elizabeta; Kirovski, Ilija; Jordanova, Olivera (Journal of Morphological Sciences, 2021)
Acute kidney injury is a sudden loss of renal function that results in deterioration of the  renalâ€™s ability to excrete urine in sufficient quantity and adequate composition. The aim of the study was to determine the incidence, risk factors and outcomes of acute kidney injury in preterm newborns. The study was conducted at the University Clinic of Pediatricsâ€“Skopje. It was a clinical, epidemiological prospective study. In the period of two years, 40 preterm newborns hospitalized at the Intensive Care Unit (ICU) with documented kidney injury were analyzed. Medical data records of hospitalized preterm infants with kidney injury were processed. The material was statistically analyzed using methods of descriptive statistics. We evaluated 40 preterm newborns with documented acute kidney injury, who at the period of 2 years were treated in the ICU. The prevalence of kidney injury was 6.9%. Most of the involved preterm newborns were male (72%), and born at 32 to 37 weeks with low birth weight (58%). Prerenal injury was evaluated in 79.5% of the cases. The mortality rate was 36% and it was significantly higher in the group of preterm infants born under 28 weeks, with Extremely Low Birth Weight Newborns ELBW. (P=0.01). Acute kidney injury is a life threatening condition with a still high mortality rate. Appropriate treatment of kidney injury in newborns with ELBW improves the outcomes and reduces the mortality of the disease. Key words : acute kidney injury, preterm newborns, ELBW https://doi.org/10.55302/JMS2141040nt